Family perception of adolescents about care in the drug consumption context - Sena, Edite Lago da Silva (2018)
The study aimed to comprehend how care related to drug consumption is perceived by family members of high school students, according to thoughts of Maurice Merleau-Ponty. We conducted the studyin the first semester of 2015, in the homes of 14 family members of students of a public school located in the inner state of Bahia, Brazil, through the phenomenologicalinterview. We submitted the experiences described to the Analytical Ambiguitytechnique.Theresults revealed the need for the family and the school to participate in the care related to drug consumption, aiming to build healthier life projects collectively. At the same time, data pointed to the importance to strengthen the harm reduction policy. The study contrasts the objectivist view aboutthe theme and shows the importance of inter-sectoralactions for a more effective human care in the context of drugs consumption.